Estudos in silico aplicados a compostos orgânicos de mercúrio e selênio em sistemas biológicos - Nogara, Pablo Andrei (2020)
Methylmercury (MeHg) is a potent neurotoxin, which is associated with the inhibition of Glutathione Peroxidase (GPx) and Thioredoxin Reductase (TrxR) selenozymes, however, the mechanism of MeHg inhibition, at the molecular level, need to be elucidated. Organic selenium compounds, such as Ebselen (Ebs) and diphenyl diselenide (DPDSe), have shown promising results against MeHg toxicity. On the other hand, organoselenium compounds can also be considered toxic, since they are able to oxidize the thiol groups from the mammalian δ-aminolevulinic acid dehydratase (δ-AlaD). The use of in silico tools, such as molecular docking, homology modeling, and DFT calculations are important because they allow analysis at the molecular level. In addition, new synthetic molecules can be designed and virtually tested. Thus, the present work aims to understand, at the molecular level, the chemical interactions involved between organoselenium and MeHg molecules with their biological targets, as well as, to propose new and more effective compounds. The results of molecular docking with GPx and TrxR demonstrated that MeHg is capable of interacting in its active sites, where a nucleophilic attack from selenocysteine residue (Sec), could lead to the formation of the Sec-SeHgMe adduct, inhibiting the enzymes. DFT calculations suggest that Sec-SeHgMe could undergo β-elimination, leading to the dehydroalanine (Dha). The interactions between organoselenium compounds and δ-AlaD showed that selenoxides are more reactive than their respective selenides, and they have Zn...O coordination, which could facilitate the attack of the Cys124 thiolate on the Se atom. New compounds, such as pyridinyl(quinolyl)-thio(seleno)semicarbazides and Ebs derivatives are proposed for therapeutic purposes. These data help us to understand the toxicology of MeHg and organoselenium molecules and can guide the development of new Hg chelating agents with high selectivity and with less adverse effects.